Bentuk dan Dampak Bullying pada Peserta Didik Tingkat Sekolah Dasar - Sari, Rizka Puspita; Tanod, Mareyke Jessy; Bulantika, Siti Zahra (Lentera: Jurnal Ilmiah Kependidikan, 2023)
The aim of this research is to determine the types and impacts of bullying on students at the elementary school level. The research was conducted at SD Negeri 1 Serdang, South Lampung. This research uses a qualitative research method with a phenomenological approach. Determining the subjects used purposive sampling of 2 students who were victims of bullying. The research results show that the types of bullying experienced by victims of bullying are physical bullying, verbal bullying and psychological bullying. Meanwhile, the impacts experienced by victims of bullying are physical and psychological impacts.